Patient burden of colonoscopy after positive fecal immunochemical testing for colorectal cancer screening - Denters, M. J.; Deutekom, M.; Bossuyt, P. M.; Fockens, P.; Dekker, E. (Endoscopy, 2013)
Background: Irrespective of the primary test used in colorectal cancer (CRC) screening, colonoscopy needs to be performed in positive screenees. This procedure is generally perceived as burdensome. We aimed to explore the burden of the colonoscopy in fecal immunochemical test (FIT)-positive screenees. Trial Registration Number: NTR1327.Methods: Two weeks after their colonoscopy, a random sample of screenees in the Dutch CRC screening pilot who underwent colonoscopy after a positive FIT were asked to rate their experience on a five-point scale (1 = not at all, 5 = very) for embarrassment, pain, and burden. Aspects that would add to satisfaction and the level of disturbance of daily activity and sleep were also assessed.Results: Of 373 invited individuals, 273 (73 %) completed the questionnaire; 53 % were men, mean age was 63 years (standard deviation [SD] 7). The bowel preparation received the highest burden score (mean score 2.87, SD 1.28) and was chosen as the most burdensome aspect by 56 %. The highest levels of pain were assigned to postcolonoscopy abdominal complaints (2.55, SD 1.03). The procedure was rated as only slightly embarrassing (1.49, SD 0.68). Adequate explanation of the procedure, immediate discussion of preliminary colonoscopy results, and a short waiting time between FIT result and colonoscopy were selected most often as potential contributors to satisfaction.Conclusion: Bowel preparation and postcolonoscopy abdominal complaints are experienced as the most burdensome elements by persons undergoing colonoscopy in a FIT screening program. A more easily tolerable bowel preparation, carbon dioxide insufflation, and adequate and timely communication are seen as measures to alleviate the burden and increase satisfaction with the procedure.